Entrepreneurial marketing and hybrid entrepreneurship: the case of JM Reid Bamboo Rods. Issue 9 (13th June 2019) - Ferreira, Caitlin C.; Lord Ferguson, Sarah; Pitt, Leyland F.
ABSTRACT: Through the presentation of the case of James Reid, a hybrid entrepreneur that transitioned towards full-time entrepreneurship, this paper discusses a number of entrepreneurial marketing issues faced by a small business. When presented with several opportunities for business growth, Reid evaluates the extent to which growth could impact his business model, brand image and his passion. The case study demonstrates the importance of maintaining brand values and establishing a clear strategic orientation in order to create a strong brand. However, these are shown to also significantly limit the growth prospects of the business. The discussion of the case delves into these issues together with an examination of the entrepreneurial journey of a highly skilled transitory hybrid entrepreneur. This paper further introduces the concept of a comfort entrepreneur, one that willingly halts the growth of their venture, and examines the business implications thereof.